Repeatability and Validity of Peripheral Refraction with Two Different Autorefractors. Issue 6 (June 2020) - Morrison, Ann M.; Mutti, Donald O.
Abstract : SIGNIFICANCE: The Welch Allyn SureSight (Welch Allyn, Skaneateles Falls, NY) and Plusoptix PowerRefractor (Plusoptix, Nuremberg, Germany) are often used with infants, but little is known about the repeatability and validity of their peripheral refractive error measurements. Selecting the best instrument will support future refractive error and emmetropization studies. PURPOSE: The purpose of this study was to determine the validity and repeatability of peripheral refractive error measurements and peripheral refraction profiles measured with the Welch Allyn SureSight and Plusoptix PowerRefractor compared with the criterion standard Grand Seiko WR-5100K (Grand Seiko Co., Hiroshima, Japan). METHODS: Cycloplegic (tropicamide 1%) autorefraction was measured in the right eyes of 21 adult subjects (31.4 ± 10.4 years) with the three instruments in randomized order on two separate visits, at least 24 hours apart, centrally, and at 30 and 20° temporal and nasal gaze. RESULTS: The SureSight measurements were within 0.24 D and not significantly different from the Grand Seiko WR-5100K in any gaze ( P < .65), whereas the PowerRefractor measurements were more myopic by as much as −0.97 D and significantly different in four of the five gaze directions ( P < .04). The 95% limits of agreement between occasions by gaze ranged from ±0.38 to ±0.61 D for the SureSight, similar to or slightly better than the WR-5100K (±0.31 to ±1.51 D) and the PowerRefractor (±0.72 to ±1.71 D). There were no significant differences between visits for any instrument in any gaze ( P < .94). The repeatability of the SureSight was also better than that for the Grand Seiko when peripheral refraction was represented by quadratic fits to the data. CONCLUSIONS: These findings suggest that the Welch Allyn SureSight is the most suitable portable autorefractor to use to monitor peripheral autorefraction based on better repeatability between occasions and better validity compared with the criterion standard Grand Seiko WR-5100K.